Did Uganda's corporate tax incentives benefit the Ugandan economy or only the firms? - Nicholas Musoke; Tereza Palanská; Caroline Schimanski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Uganda has one of the lowest corporate income tax collection rates in sub-Saharan Africa, while offering generous corporate tax incentives. It is unclear whether tax incentives achieve their objectives without primarily benefiting firms, potentially undermining domestic revenue mobilization and encouraging tax avoidance. Using Uganda's administrative tax data for 2014-21 and a new tax incentive dataset, this study shows that tax holidays and the reintroduction of investment allowances are associated with a significant increase in investment and mostly with higher workforce-related expenses. However, there is no clear evidence of a causal link with these incentives, while tax holidays can cost Uganda over UGX160 billion annually, corresponding to 0.12 per cent of GDP, thus demanding further research. In addition to guidance for Ugandan policy-makers on the effect of particular tax incentives, the results also highlight the importance of assessing impacts and systematic use of administrative tax data for evidence-based policymaking in developing countries.
Keywords: F63; H25; H26; O23; 330; corporate tax incentives; domestic revenue mobilization; administrative tax data; developing countries; tax avoidance